2023
DOI: 10.2147/dhps.s383130
|View full text |Cite
|
Sign up to set email alerts
|

Safety Aspects and Rational Use of Testosterone Undecanoate in the Treatment of Testosterone Deficiency: Clinical Insights

Abstract: Testosterone deficiency is diagnosed by a serum total testosterone level below 300 ng/dL in combination with symptoms such as decreased energy and libido. These symptoms can be ameliorated by restoring serum testosterone to the physiologic range with testosterone therapy (TT). There are numerous forms of testosterone therapy, such as injectable, transdermal, nasal, and subcutaneous applications. There are also multiple formulations of injection, such as testosterone cypionate, testosterone enanthate, and testo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Additional research, such as the study by Harle, Basaria, and Dobs, (2005) on the use of testosterone undecanoate, supports this approach, revealing that no significant changes in liver function were detected, and biochemical tests remained stable throughout the treatment. These findings are reinforced by further studies that observed no notable impacts on liver function as a result of androgen treatment (Harle, Basaria, and Dobs, 2005;Moon et al, 2010;Campbell et al, 2023).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Additional research, such as the study by Harle, Basaria, and Dobs, (2005) on the use of testosterone undecanoate, supports this approach, revealing that no significant changes in liver function were detected, and biochemical tests remained stable throughout the treatment. These findings are reinforced by further studies that observed no notable impacts on liver function as a result of androgen treatment (Harle, Basaria, and Dobs, 2005;Moon et al, 2010;Campbell et al, 2023).…”
Section: Discussionmentioning
confidence: 74%
“…For example, there is an increase in the enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT), a decline in the concentration of plasma proteins synthesized in the liver such as albumin, and an increase in total cholesterol and LDL (Low Density Lipoprotein), with a decrease in HDL (High Density Lipoprotein) (Hartgens et al, 2004) Disturbances in the urinary tract can also be observed, as testosterone is responsible for excreting most of the products obtained in metabolism and controlling the majority of the constituents of body fluids (Guyton and Hall, 2011). Androgen abuse may trigger an increase in creatinine, urea, and uric acid, sodium retention, an increase in nitrogen balance, and an elevation in the enzyme creatine kinase (CK) (Zhao, Moon, and Park, 2013;Sahlin et al, 2015;Campbell et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone formulations also vary across countries. For example, a 1000 mg testosterone undeconoate preparation is marketed in Europe (Nebido®, Bayer, Berkshire, United Kingdom), while the closest equivalent in the United States is a 750 mg testosterone undeconate preparation (Aveed®, Endo International, Malvern, PA, United States) [ 32 ]. For those using testosterone topical gel, contamination of the venipuncture site by gel has previously been reported in a few case reports [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…171 In the marketed oral capsules of Andriol, Jatenzo, Tlando, and Kyzatrex, liquids of oils and surfactants are used for emulsification in the gastrointestinal tract to enhance lymphatic absorption of the drug. 172 In a clinical study, Andriol showed 10-fold higher bioavailability after a standard breakfast compared with the fasting state, which indicated that the product must be taken with meals for proper absorption. 173 A study comparing clinical reports of oral, intramuscular, and transdermal testosterone formulations showed that all DDS have similar efficacy.…”
Section: Site-and Amount-controlled Ddsmentioning
confidence: 99%
“…Although testosterone shows very low oral bioavailability, formulations of the fatty acid ester of testosterone undecanoate show increased bioavailability of about 3%, in which the contribution of lymphatic transport was more than 90% . In the marketed oral capsules of Andriol, Jatenzo, Tlando, and Kyzatrex, liquids of oils and surfactants are used for emulsification in the gastrointestinal tract to enhance lymphatic absorption of the drug . In a clinical study, Andriol showed 10-fold higher bioavailability after a standard breakfast compared with the fasting state, which indicated that the product must be taken with meals for proper absorption …”
Section: Site- and Amount-controlled Ddsmentioning
confidence: 99%